A mixed-methods study exploring the characteristics and needs of long-stay patients in high and medium secure settings in England: implications for service organisation - Birgit Völlm; Rachel Edworthy; Jessica Holley; Emily Talbot; Shazmin Majid; Conor Duggan; Tim Weaver; Ruth McDonald (National Institute for Health Research, 2017)
Background: Forensic psychiatric services provide care for those with mental disorders and offending behaviour. Concerns have been expressed that patients may stay for too long in too high levels of security. The economic burden of these services is high, and they are highly restrictive for patients. There is no agreed standard for 'long stay'; we defined a length of stay exceeding 5 years in medium secure care, 10 years in high secure care or 15 years in a combination of both settings as long stay. Objectives: To (1) estimate the number of long-stay patients in secure settings; (2) describe patients' characteristics, needs and care pathways and the reasons for their prolonged stay; (3) identify patients' perceptions of their treatment and quality of life; and (4) explore stakeholders' views on long stay. Design: A mixed-methods approach, including a cross-sectional survey (on 1 April 2013) of all patients in participating units to identify long-stay patients [work package (WP) 1], file reviews and consultant questionnaires for long-stay patients (WP2), interviews with patients (WP3) and focus groups with other stakeholders (WP4). Setting: All three high secure hospitals and 23 medium secure units (16 NHS and 9 independent providers) in England. Participants: Information was gathered on all patients in participating units (WP1), from which 401 long-stay patients were identified (WP2), 40 patients (WP3), 17 international and 31 UK experts were interviewed and three focus groups were held (WP4). Results: Approximately 23.5% of high secure patients and 18% of medium secure patients were long-stay patients. We estimated that there are currently about 730 forensic long-stay patients in England. The source of a patient's admission and the current section of the Mental Health Act [Great Britain. Mental Health Act 1983 (as Amended by the Mental Health Act 2007). London: The Stationery Office; 2007] under which they were admitted predicted long-stay status. Long-stay patients had complex pathways, moving 'around' between settings rather than moving forward. They were most likely to be detained under a hospital order with restrictions (section 37/41) and to have disturbed backgrounds with previous psychiatric admissions, self-harm and significant offending histories. The most common diagnosis was schizophrenia, but 47% had been diagnosed with personality disorder. Only 50% had current formal psychological therapies. The rates of violent incidents within institutions and seclusion were high, and a large proportion had unsuccessful referrals to less secure settings. Most patients had some contact with their families. We identified five classes of patients within the long-stay sample with different characteristics. Patients differed in their attribution of reasons for long stay (internal/external), outlook (positive/negative), approach (active/passive) and readiness for change. Other countries have successfully developed specific long-stay services; however, UK experts were reluctant to accept the reality of long stay and that the medical model of 'cure' does not work with this group. Limitations: We did not conduct file reviews on non-long-stay patients; therefore, we cannot say which factors differentiate between long-stay patients and non-long-stay patients. Conclusions: The number of long-stay patients in England is high, resulting in high resource use. Significant barriers were identified in developing designated long-stay services. Without a national strategy, these issues are likely to remain. Future work: To compare long-stay patients and non-long-stay patients. To evaluate new service models specifically designed for long-stay patients. Study registration: The National Institute for Health Research (NIHR) Clinical Research Network Portfolio 129376. Funding: The NIHR Health Services and Delivery Research programme.